Architectural Planning of Outpatient Registration and Queue Information System using Enterprise Architecture Planning at the Hospital - Putu Widiadnyana; Andreyana, Putu Veda (Program Studi Teknologi Informasi, Fakultas Teknik, Universitas Udayana, 2025)
Advances in information technology have encouraged healthcare organizations to develop integrated information systems that are aligned with their business processes. However, many institutions still face problems such as unintegrated systems, data duplication, and mismatches between business needs and information technology. These conditions highlight the need for architectural planning as the basis for structured and sustainable information system development. This study aims to develop an Enterprise Architecture for outpatient services with reference to Enterprise Architecture Planning (EAP). The research methods include literature study, analysis of existing conditions, business process modeling, and data, application, and technology architecture design. The results of this study are an enterprise architecture blueprint that is expected to be a reference for the development of integrated and efficient hospital services that support service quality improvement and management decision making.